Future of the Artificial Intelligence: Object of Law or Legal Personality? - I. A. Filipova; V. D. Koroteev (Journal of Digital Technologies and Law, 2023)
Objective: to reveal the problems associated with legal regulation of public relations, in which artificial intelligence systems are used, and to rationally comprehend the possibility of endowing such systems with a legal subject status, which is being discussed by legal scientists.Methods: the methodological basis of the research are the general scientific methods of analysis and synthesis, analogy, abstraction and classification. Among the legal methods primarily applied in the work are formal-legal, comparative-legal and systemic-structural methods, as well as the methods of law interpretation and legal modeling.Results: the authors present a review of the state of artificial intelligence development and its introduction into practice by the time of the research. Legal framework in this sphere is considered; the key current concepts of endowing artificial intelligence with a legal personality (individual, collective and gradient legal personality of artificial intelligence) are reviewed. Each approach is assessed; conclusions are made as to the most preferable amendments in the current legislation, which ceases to correspond to the reality. The growing inconsistency is due to the accelerated development of artificial intelligence and its spreading in various sectors of economy, social sphere, and in the nearest future – in public management. All this testifies to the increased risk of a break between legal matter and the changing social reality.Scientific novelty: scientific approaches are classified which endow artificial intelligence with a legal personality. Within each approach, the key moments are identified, the use of which will allow in the future creating legal constructs based on combinations, avoiding extremes and observing the balance between the interests of all parties. The optimal variant to define the legal status of artificial intelligence might be to include intellectual systems into a list of civil rights objects, but differentiating the legal regulation of artificial intelligence as an object of law and an “electronic agent” as a quasi subject of law. The demarcation line should be drawn depending on the functional differences between intellectual systems, while not only a robot but also a virtual intellectual system can be considered an “electronic agent”.Practical significance: the research materials can be used when preparing proposals for making amendments and additions to the current legislation, as well as when elaborating academic course and writing tutorials on the topics related to regulation of using artificial intelligence.